Desempenho produtivo e derivação dos coeficientes de cultura da canola usando parâmetros biofísicos das plantas - Silva, Clarissa Moraes da (2022)
Oilseed crops are commonly used in crop rotation in southern Brazil due to their high economic return for farmers. Canola is used by the industry as sources of oil content and for the biodiesel market. Although irrigation is frequently not used in the region, the high variability of precipitation both in terms of quantity and timing may lead to water stress during the most sensitive stage (flowering to grain maturity) which negatively impacts yield. Thus, supplemental irrigation should be scheduled to avoid these situations. Several approaches may be used to support irrigation schedule such as the FAO56 two step approach in which the crop water use or crop evapotranspiration (ETc) is estimated from the reference crop evapotranspiration (ETo) and a crop coefficient (Kc). ETo represents the actual evaporative demand of the atmosphere while Kc represents the characteristics that distinguish the crop from the grass reference. Therefore, the approach requires estimation and local adjustments of Kc along the crops season. Recently, new approaches have been developed to estimate Kcs from observations of the vegetation, such as the Allen and Pereira (2009) (A&P) approach which uses the fraction of the ground covered by the crop canopy (fc), leaf area index (LAI), and crop height. Thus, the objective of the current study was to estimate the crop coefficient from leaf area index and crop height for irrigated canola. Experiments were carried out during the 2020 and 2021 growing seasons. The Kcb values for each growth stage (Kcb ini, Kcb dev, Kcb med, and Kcb end) were previously estimated using a density coefficient (Kd), which was computed from the LAI and crop height (h) observed at the same dates. The results show the model ability to estimate soil water dynamics, with b0 values ranging from 0.97 to 1.04 and RMSE < 5% of the TAW. Kcb A&P calibration using SIMDualKc demonstrated that biophysical characteristics can be used to estimate canola water use, with R2 > 0.86 and b0 between 0.93 and 1.01. Canola grain yield and oil content were higher when the available soil water (ASW) was kept at 50% of the TAW, than full irrigated plants (80% of the TAW). In addition, the soil water balance model SIMDualKc, which applies the FAO56 methodology and allows partition ETc into soil evaporation and crop transpiration was calibrated and validated using the observed crop data and soil moisture. Results show the good ability of the model for estimating the soil water dynamics. When comparing both approaches results show the adequacy and easiness of use of the A&P approach to support irrigation scheduling for one of the oilseed crops used in Southern Brazil.